Hand suture versus stapler for closure of loop ileostomy: a systematic review and meta-analysis of randomized controlled trials - Löffler, Thorsten; Rossion, Inga; Goossen, Käthe; Saure, Daniel; Weitz, Jürgen; Ulrich, Alexis; Büchler, Markus W.; Diener, Markus K. (Langenbeck's archives of surgery, 2015)
The aims of this study are to compare the 30-day rate of bowel obstruction for stapled vs. handsewn closure of loop ileostomy, and to further assess efficacy and safety for each technique by secondary endpoints such as operative time, rates of anastomotic leakage, and other post-operative complications within 30 days.